1987
DOI: 10.2307/3899605
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Selection, Foraging Behavior, and Dietary Nutrition of Elk in Burned Aspen Forest

Abstract: Prescribed burning is frequently used to enhance regeneration of aspen. The effects of burning aspen on wild ungulates are poorly understood. We used free-ranging tame elk to assess diet composition and quality on a site containing a 40-ha aspen burn, pure unburned aspen, mixtures of aspen and conifers, and other habitats. Foraging preferences of eik among the habitats were also investigated. Overall, no dietary nutritional differences were found between burned and unburned aspen habitats. Diet composition by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
1

Year Published

1990
1990
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(41 citation statements)
references
References 3 publications
2
38
1
Order By: Relevance
“…Cook [21] Improving forage quality can be used to lure cattle to a feeding site. Burning removes standing dead and makes forage more attractive to large herbivores [17,58]. Applying nitrogen fertilizer can increase forage utilization from two [27] up to five times [38] the level of unfertilized areas.…”
Section: Predicting Grazing Distributionmentioning
confidence: 99%
“…Cook [21] Improving forage quality can be used to lure cattle to a feeding site. Burning removes standing dead and makes forage more attractive to large herbivores [17,58]. Applying nitrogen fertilizer can increase forage utilization from two [27] up to five times [38] the level of unfertilized areas.…”
Section: Predicting Grazing Distributionmentioning
confidence: 99%
“…Data were collected on dietary composition, foraging efficiency, and dietary quality using bite-count methods (Canon andothers 1987, Wickstrom andothers 1984).…”
Section: Evidence Of Feedback Effects On Ungulate Productivity In Thementioning
confidence: 99%
“…Rejuvenation of these stands is critical, because only 7% of the estimated 479,000 acres (193,850 ha) of aspen in Arizona and New Mexico is in the seedling and sapling stage; the rest are mature or overmature (Patton and Jones 1977). A survey of aspen over the West has indicated that without management intervention seral aspen stands will probably be replaced by conifers, and stable ones may become all-aged and less productive (DeByle et al 1987). Although relatively stable aspen stands have been identified in other areas of the Rocky Mountains (Harniss and Harper 1982), those in the Southwest are seral and will be eventually replaced by conifers, perhaps at a faster rate than those in western Colorado.…”
Section: Montane Conifer Forest (Mixed Conifer Series) Rocky Mountainmentioning
confidence: 99%
“…They concluded clearcutting aspen in small blocks on an 80-year rotation would increase "edge," species diversity, and even total number of birds. Canon et al (1987) compared elk foods and feeding habits among several habitats, including burned and unburned aspen stands and mixtures of aspens and conifers. They found no dietary nutritional differences between burned and unburned aspen stands but did note that time spent feeding was substantially greater on burned aspen sites, probably because preferred forages were consistently available.…”
Section: Montane Conifer Forest (Mixed Conifer Series) Rocky Mountainmentioning
confidence: 99%